The identification of novel small extracellular vesicle (sEV) production modulators using luciferase‐based sEV quantification method. Issue 9 (27th September 2022) - Yamamoto, Aki; Takahashi, Yuki; Inuki, Shinsuke; Nakagawa, Shumpei; Nakao, Kodai; Ohno, Hiroaki; Doi, Masao; Takakura, Yoshinobu
Abstract: Small extracellular vesicles (sEVs) are nano‐sized vesicles secreted from various cells that contain bioactive metabolites and function as key regulators for intercellular communication. sEVs modulate diverse biological and pathological processes in the body, and the amount of circulating sEVs has been reported to correlate with certain disease progression. Therefore, the identification of small molecular compounds that can control sEV production may become a novel therapeutic strategy. In this study, a rapid, highly sensitive sEV quantification method utilizing fusion proteins consisting of Gaussia luciferase (gLuc) reporter protein and sEV markers (CD63 and CD82) was developed. A total of 480 compounds were screened to identify potent inducers and inhibitors of gLuc activity. Two novel compounds, KPYC08425 and KPYC12163, showed significant and dose‐dependent changes in gLuc activity with minimal cytotoxicity based on the LDH assay. The efficacy of these two compounds was further evaluated by protein quantification of the isolated sEVs. Further evaluation of KPYC12163 suggested that the autolysosomal pathway may be involved in its inhibitory effect on sEV production.